Hak Waris Anak Diluar Nikah: Implementasi Menurut Hukum Perdata Indonesia - Cepi Winarso; Dika Ratu Marfu’atun; Santy Fitnawati WN; Ahmad Fauzan (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
According to the provisions of the Covenant, if the unmarried child is not recognised by his father or his mother, he shall be deemed not to have a legal relationship with his parents. Therefore, if a child is recognized and followed by the confirmation of the child from his parents, the child may inherit the inheritance of the parent who acknowledges it, with the division of the legacy prescribed by law. Under the Marriage Act, Act No. 1 of 1974 (Article 43, para. (1)), unrecognized children automatically have civil relations with their mothers and their families. The right and status of the out-of-marriage child to the inheritance of the parent who acknowledges it at the confirmation of the child is basically the same as the legal child. The recognized and certified off-marital child is the heir who has the same rights as the child born in a legitimate marriage.